Carotid Extra-Media Thickness in Children: Relationships With Cardiometabolic Risk Factors and Endothelial Function - Pacifico, Lucia; Perla, Francesco Massimo; Tromba, Luciana; Carbotta, Giovanni; Lavorato, Michela; Pierimarchi, Pasquale; Chiesa, Claudio (Frontiers in Endocrinology, 2020)
Background: Emerging evidence suggests that structural adventitial modifications and perivascular adipose tissue (PAT) may have a role in early atherogenesis. In a cohort of children and adolescents, we explored 1) the association of carotid extra-media thickness (cEMT), an ultrasound measure whose main determinants are arterial adventitia and PAT, with obesity and its cardiometabolic complications; and 2) the interplay between cEMT and endothelial function. Methods: The study participants included 286 youths (age, 6-16 years; 154 boys, and 132 girls). Anthropometric and laboratory parameters, liver ultrasound, vascular structure measures [cEMT and carotid intima-media thickness (cIMT)], endothelial function [brachial artery flow-mediated dilation (FMD)] were obtained in all subjects. Nonalcoholic fatty liver disease (NAFLD) was diagnosed in the presence of hepatic fat on ultrasonography, in the absence of other causes of liver disease. Diagnosis of metabolic syndrome (MetS) was established on the basis of three or more of the following cardiovascular disease (CVD) risk variables: abdominal obesity, high triglycerides, low high-density lipoprotein cholesterol, elevated blood pressure (BP), and impaired fasting glucose. Results: cEMT demonstrated significant associations with body-mass index (BMI) and waist circumference (WC), BP, insulin resistance, NAFLD, and inflammation. No association was found between cEMT and lipid values, and between cEMT and MetS. A stepwise multivariate linear regression analysis indicated that WC (β coefficient, 0.35; P< 0.0001) was the only determinant of cEMT, independently of other major cardiometabolic risk factors. Further adjustment for cIMT did not significantly alter this association. FMD was correlated to age, Tanner stage, total and abdominal obesity, BP, NAFLD, and cEMT. The association between FMD and cEMT was independent of age, sex, Tanner stage, WC, and BMI (β coefficient, -0.14; P= 0.027). After controlling for CVD risk factors and basal brachial artery diameter, cEMT remained associated with FMD (β coefficient, -0.11; P= 0.049). Conclusions: In youths, cEMT is associated with abdominal fat, a well established body fat depot with important implications for cardiovascular diseases. Furthermore, cEMT is related to FMD, suggesting that arterial adventitia and PAT may be involved in the early changes in endothelial function.